Ectoparasite Investigation on Bats in Universiti Tun Hussein Onn Malaysia, Johor - Mohd Rasli, Fatin Nursyamimi; Sapaat, Arney (Enhanced Knowledge in Sciences and Technology, 2026)
Bats are widely distributed in both natural and human-modified landscapes in Malaysia. However, information on bat-associated ectoparasites in semi-urban environments remains limited. This study investigated bat host diversity, ectoparasite diversity, host-ectoparasite associations, and infestation rates at Universiti Tun Hussein Onn Malaysia (UTHM), Johor. Bat sampling was conducted at UTHM Parit Raja and Tanjung Labuh Aerodrome using mist nets during dusk and night hours. Captured bats were identified morphologically and examined for ectoparasites, which were collected and identified by standard morphological keys. Four bat species belonging to two families were recorded  at UTHM Parit Raja, specifically Cynopterus brachyotis, Cynopterus horsfieldii, Eonycteris spelaea, and Murina suilla. Five ectoparasite taxa were identified, consisting of four species of nycteribiid bat flies and mites from the genus Macronyssus.  The overall ectoparasite infestation rate was 43.3%, with higher infestation observed among Cynopterus sp. No bats were captured at Tanjung Labuh due to the open habitat structure, although bat activity was observed. This study provides baseline information on bat-ectoparasite interactions in semi-urban environments.